MONITORING OF DEFORMATIONS IN AN ABOVE-GROUND GAS PIPELINE USING 3D SCANNING - Романюк, Володимир (SWorldJournal, 2025)
The article presents the results of spatial monitoring of the technical condition of Ukraine’s gas transmission system using modern geodetic technologies, particularly terrestrial 3D laser scanning. The research was conducted on an above-ground gas pipeli